Feminist organization in Concepción, Chile (2016-2019). A reflection situated from Joan Scott’s notion of experience. - Inostroza Boitano, Camila Elena (Re-presentaciones: Periodismo, comunicación y sociedad, 2022)
Through the analysis of the historical context and a semi-structured interview with a feminist activist, the common elements and critical knots regarding the feminist political organization in the city of Concepción between 2016 and 2019 are visualized. The notion of experience proposed by Joan Scott (2001) is used to understand what emerges from the interview not as an incontrovertible speech but as that experience that transforms the subjects, and is produced by a specific historicity. It is concluded that there would be constitutive but dynamic elements of the feminist movement in Chile.